Structural changes of Maribor economy after year 1991 - Lorber, Lučka (Journal for Geography, 2006)
Structural changes of Maribor economy after year 1991 The article deals with structural changes of Maribor economy in the transition period and during the time of Slovenia’s joining to the Common European Market. Emphasis is given to the effects of negative deindustrialization that the city has gone through in the process of transition to market economy. Together with the first signs of crisis in leading manufacturing activities there was a large number of the unemployed and decrease in income of Maribor economy in the gross domestic product of the state. Based on the analysis of the economic structural changes during the period between years 1991 and 2004 it can be established that the key reason for stagnant development of the Maribor economy lies in low investment rates that reached merely 90 per cent of the republic average in that period. Economic growth was hindered also by low added value per employee, inadequate demographic picture of the population and the lack of economic strategy of the city.